THE IMPLEMENTATION OF PORT MANAGEMENT POLICY IN PELINDO III TANJUNG PERAK SURABAYA - Sony Kunila; Budi Rianto; Viv Djanat Prasita; Lunariana Lubis (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Research on the implementation of the Port Implementation policy at Pelindo III Tanjung Perak Surabaya (Case study of the Implementation of the Minister of Transportation's Regulation Number: PM 146 of 2016 concerning changes to the Minister of Transportation's regulation PM Number 51 of 2015 concerning the Implementation of Seaports) aims to analyze the implementation of Port Operational Policies at Pelindo III Tanjung Perak Surabaya. In addition, to analyze the factors that support and hinder the successful implementation of the Port Management in Pelindo III Tanjung Perak Surabaya. This research uses a qualitative method with a case study approach. Data collection is done through interviews, observations and documentation and then analyzed through data reduction, data presentation and conclusions. The results show that Port Management Policy in Pelindo III has been implemented between Pelindo III, Syahbandar, and other stakeholders, even though there are some inhibiting factors, such as the lack of human resource quality, the complexity of the bureaucracy in handling export and import documents and ship waiting time at port. Keywords: Implementation, Policy, Port